The Effect of Nursing Care for Client Symptoms Frequency with Sensory Perception Disorders: Auditory Hallucination in Bantur Village - Rohmi, Faizatur; Aditya, Ronal Surya (Jurnal Keperawatan, 2020)
Introduction: Hallucination is a dangerous type of mental disorder. because it has various impacts, lead to suicide, violent behavior and threaten the environment. Objective: The purpose of this study was to identify the effect of nursing care on clients with sensory perception disorders: auditory hallucinations in Bantur village. Method: The design used is One Groups Pretest-Posttest Design, with a simple random sampling technique. The sample in this study amounted to 48 respondents. Analysis of the data used in this study used the Wilcoxon test. Result: Based on the test resulted with Wilcoxon p value <0.05, which mean there was a difference in nursing care to decrease the signs of client symptoms with sensory perception disorder: auditory hallucinations. Discusion: This study concludes that nursing care has proven to be effective in reduced the signs of symptoms in patients with auditory hallucinations. The implication of nursing in this study is that nursing care becomes an important and essential thing that must be given to people with mental disorders.